Getting PPP right: Identifying mean-reverting real exchange rates in panels - Georgios Chortareas; George Kapetanios (Queen Mary University of London, Department of Economics, 2004)
Recent advances in testing for the validity of Purchasing Power Parity (PPP) focus on the time series properties of real exchange rates in panel frameworks. One weakness of such tests, however, is that they fail to inform the researcher as to which cross-section units are stationary. As a consequence, a reservation for PPP analyses based on such tests is that a small number of real exchange rates in a given panel may drive the results. In this paper we examine the PPP hypothesis focusing on the stationarity of the real exchange rates in up to 25 OECD countries. We introduce a methodology that when applied to a set of established panel-unit-root tests, allows to identify the real exchange rates that are stationary and poolable without trading-off any test power. We apply procedures that account for cross-sectional dependence. Our results reveal evidence of mean-reversion that is significantly stronger as compared to those obtained by the existing literature, strengthening the case for PPP. Moreover, our approach allows to provide half-lives estimates for the mean-reverting real exchange rates and so find that the half-lives are shorter than the literature consensus and therefore that the PPP puzzle is less pronounced than initially thought.
Keywords: C12; C15; C23; F3; 330; PPP; Real exchange rates; Half-lives; Panel unit root tests; Kaufkraftparit\~AƒÂt; Panel; Unit Root Test; Sch\~AƒÂtzung; OECD-Staaten; Mean Reversion